2016
DOI: 10.1007/s00401-016-1577-6
|View full text |Cite|
|
Sign up to set email alerts
|

Intraneuronal aggregation of the β-CTF fragment of APP (C99) induces Aβ-independent lysosomal-autophagic pathology

Abstract: Endosomal-autophagic-lysosomal (EAL) dysfunction is an early and prominent neuropathological feature of Alzheimers’s disease, yet the exact molecular mechanisms contributing to this pathology remain undefined. By combined biochemical, immunohistochemical and ultrastructural approaches, we demonstrate a link between EAL pathology and the intraneuronal accumulation of the β-secretase-derived βAPP fragment (C99) in two in vivo models, 3xTgAD mice and adeno-associated viral-mediated C99-infected mice. We present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
252
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(274 citation statements)
references
References 63 publications
19
252
1
2
Order By: Relevance
“…It was recently found that βCTF can both be a substrate for autophagic degradation and induce impairment of the autophagic/ lysosomal (29) and endosomal (30) pathways. These results, together with our findings, suggest the presence of a positive feedback mechanism in which a deficit in autophagy leads to increased βCTF levels, which can, in turn, induce further autophagic impairment.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently found that βCTF can both be a substrate for autophagic degradation and induce impairment of the autophagic/ lysosomal (29) and endosomal (30) pathways. These results, together with our findings, suggest the presence of a positive feedback mechanism in which a deficit in autophagy leads to increased βCTF levels, which can, in turn, induce further autophagic impairment.…”
Section: Discussionmentioning
confidence: 99%
“…This simplistic view of a complex disease has recently drastically evolved. Besides altered ratios in the canonical forms of Aβ40 and Aβ42 that are indeed affected in AD brain39, recent advances on the structural nature (N-terminally truncated and/or C-terminally trimmed4041, biophysical state (monomeric, multimeric, aggregated, fibrillar3442, subcellular localization (intracellular, secreted4344) of Aβ species as well as other βAPP catabolites (C99, AICD511121345, have significantly modified our view of the genuine trigger of the pathology. It arose from these studies that soluble Aβ oligomers (Aβo), appear prior to senile plaques and are now considered to be more toxic than monomeric or fibrillar Aβ.…”
Section: Discussionmentioning
confidence: 99%
“…BACE1 is considered as a key therapeutic target not only because its inhibition precludes Aβ production but also because BACE-1-mediated βAPP cleavage only, generates C99 that had been shown to trigger cellular perturbations and toxicity even in absence of Aβ in mice models of AD111213. BACE1 is highly expressed in neurons and, unlike is the case for γ-secretase, its expression increases during ageing as well as in the brain of AD patients1415.…”
mentioning
confidence: 99%
“…Different APP C-terminal antibodies confirmed the 25 kDa CTFη as the predominant band in human CSF. As stated, these APP proteolytic fragments are derived from a constitutive processing step driven by a η-secretase that is partially in dynamic equilibrium with α-and β-secretase-mediated proteolysis (Haass et al, 1992;Willem et al, 2015;Lauritzen et al, 2016). The current canonical views about APPrelated cleavage events are likely a partial understanding of the overall process.…”
Section: Discussionmentioning
confidence: 99%